Judges' Perspectives on the Determination of the Amount of Mut'ah, Childbirth Costs, and Child Sustenance in Divorce Cases (The study on the Court’s Decision Number 808/Pdt.G/2021/Pa. Kab. Kdr) - Fachrunisa, Syifa; Qamaria, Rezki Suci; Hanani, Nurul (El-Usrah: Jurnal Hukum Keluarga, 2023)
The case 808/Pdt.G/2021/PA.Kab.Kdr is a petition for divorce. The judge will order the Petitioner to pay mut'ah, maternity costs, and child support once the divorce has been finalized. The issue that will be addressed in this study is the absence of a specific regulation governing the calculation of mut'ah, maternity costs, and child support in this instance. In determining the amount of mut'ah, maternity expenditures, and child support, the Panel of Judges therefore applies ijtihad based on its opinion. The purpose of this study is to determine how the judge perceives the amount of mut'ah, maternity costs, and child support in this specific case. This is a qualitative research and socio-legal study. The quantity of mut'ah is determined by the length of the marriage and the husband's abilities, or by mutual agreement between the parties. In addition, the Panel of Judges will examine the issue of childbirth expenses so long as the prosecution can provide proof in the form of receipts or witnesses, as childbirth expenses are an obligation of the husband. Regarding child maintenance, the quantity of support that must be provided is adjusted based on the child's needs and the husband's suitability to meet them, or the parties can reach an agreement.